PREVALENCE AND DETERMINANTS OF RELAPSE AMONG PATIENTS WITH SUBSTANCE USE DISORDERS AT FEDERAL NEUROPSYCHIATRIC HOSPITAL DAWANAU, KANO - Dausayi, Bilal Bashir; Haddad, Mahfuz Muhammad; Ibrahim, Abdullahi Haruna; Bello, Umar Lawal; Yunusa, Umar; Ladan, Muhammad Awwal; Suberu, Ahmed; Aliyu, Abdulmaleek Musa; Hassan, Murtala Hassan; Abdulrashid, Idris (FUDMA Journal of Sciences, 2026)
Substance use disorders (SUD) are pattern of substance use that cause damage to physical or mental health. Relapse in SUD results in high cost of treatment and decline in functionality. The study determined the prevalence and examined the determinants of relapse among patients with SUD at Federal Neuropsychiatric Hospital Dawanau, Kano (FNPHDK). A convergent parallel mixed method was used. Total enumerative sampling techniques was used to select 694. The Quantitative data was collected using a checklist and analyzed, while a focused group discussion guide was used to collect the qualitative data which was analyzed thematically. The result revealed that, the prevalence of relapse among patients with SUD from July, 2023 to December, 2024 was 72.9%. The logistic regression analysis indicated that, Sadness (AOR: 1.707, CI: 1.193 – 2.443), stressful life events (AOR: 2.243, CI: 1.394 – 3.610) lack of adherence to medication (AOR: 1.459, CI: 1.030 – 2.065), failure to follow up (AOR: 1.783, CI: 1.212 – 2.625) and, family conflict (AOR: 1.641, CI: 1.092 – 2.466) were the significant triggers of relapse (P0.05). Findings for both quantitative and qualitative data sets converged with lack of medication adherence as the determinant of relapse The researcher concludes that there is need to consider  medication adherence during treatment, therefore recommends that, new policies/ strategies such as educating the patients and the caregivers on the importance of medication to decrease the risk of relapse.
Keywords: Determinants; Relapse; Patients; Substance use disorder